2020
DOI: 10.3390/dj8040112
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Primary Stability, Histomorphometric Findings, and Bone Density: A Prospective Randomized Study after Alveolar Ridge Preservation with a Collagen Cone

Abstract: Background: The objective of this investigation was to examine whether determination of bone density (BD) with a cone beam computed tomography (CBCT) scan could help predict the primary stability (PS) of the implants and to investigate whether associations between the histomorphometric findings and the CBCT scan could be observed. Materials and methods: In this randomized clinical study, the efficacy of alveolar ridge preservation (ARP) with a combination of a collagen cone and a collagen membrane procedure af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Abdulkarim et al reported on the correlation between CBCT bone GVs and clinical bone quality, which was stronger in the absence of bone grafting material and weaker with graft, especially xenograft [49]. In our research, the grafting material was completely absorbable, so it was not affecting the measurements [50]. Moreover, numerous papers backing a correlation between CBCT-derived bone GVs and primary and secondary implant stability, which is a clinically significant parameter, were published [51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Abdulkarim et al reported on the correlation between CBCT bone GVs and clinical bone quality, which was stronger in the absence of bone grafting material and weaker with graft, especially xenograft [49]. In our research, the grafting material was completely absorbable, so it was not affecting the measurements [50]. Moreover, numerous papers backing a correlation between CBCT-derived bone GVs and primary and secondary implant stability, which is a clinically significant parameter, were published [51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 46%
“…Moreover, numerous papers backing a correlation between CBCT-derived bone GVs and primary and secondary implant stability, which is a clinically significant parameter, were published [51][52][53][54][55]. Nevertheless, the literature data on those correlations are ambiguous, which has to be taken into consideration when drawing conclusions [50].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 47 were excluded from the analysis. Finally, 26 studies were included in this review, which consisted of 17 prospective cohort studies, eight retrospective cohort studies, and one non‐randomized controlled trial (Aksoy et al., 2009; Arisan et al., 2012; Bergkvist et al., 2010; Bruno et al., 2018; Chatvaratthana et al., 2017; Cortes et al., 2015; de Elío Oliveros et al., 2020; Farré‐Pagès et al., 2011; Hakim et al., 2019; Ikumi & Tsutsumi, 2005; Ivanova et al., 2021; Kim et al., 2021; Merheb et al., 2010, 2016, 2018; Mikic et al., 2021; Miyamoto et al., 2005; Schnitman & Hwang, 2011; Schnutenhaus et al., 2020; Sennerby et al., 2015; Song et al., 2009; Takechi et al., 2020; Tanaka et al., 2018; Tatli et al., 2014; Triches et al., 2019; Turkyilmaz & McGlumphy, 2008). A total of 3109 implants placed in 1171 were analyzed in this review.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Osteology Consensus Report of 2012, based on the systematic review by Vignoletti et al 2012 [ 8 ], performing a socket preservation procedure allows the volume of the existing soft and hard tissue to be preserved. The duration of time between the ARP measure and the implant placement must be considered an important factor [ 9 ]. Socket preservation procedures enhance functional and aesthetic outcomes, thus avoiding subsequent difficulties in prosthetic rehabilitation and the placement of dental implants in the area [ 10 ].…”
Section: Introductionmentioning
confidence: 99%